Demand analysis Pharmaceutical products Industry (druggeneric) in Pharmacies in district Bangkinang - Aditia, Chandra; Harahap, Azwar; Richard, Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in the District Bangkinang that discuss DemandAnalysis Pharmaceutical Products (Generic Drugs) In the Pharmacy in District Bangkinang, the method used in this research is descriptive and the type of data used is primary data and secondary data.Research variable is Demand Analysis Pharmaceutical Production (GenericDrugs) In the Pharmacy in District Bangkinang as the dependent variable, the price of the drug itself, the number of people who are sick, and income as independent variables. The formulation of the problem is to see how the effect of independent variables (independent) variables are not independent to (dependent).The factors that affect the demand for generic drugs in the District Bangkinang is a factor in the price of generic drugs is the number of sick people in the District Bangkinang. And factor income people should have no effect because of the demand for generic drugs are widely used for people with low income but inversely as more middle and upper income earners that generic drug receipts, so the third factor does not affect the demand for generic drugs.Key words: the price of the drug itself, the number of people who are sick, and income.